LEXICOGRAPHIC CHALLENGES IN BILINGUAL TERMINOLOGY: A COMPARATIVE STUDY OF LINGUISTIC TERMS IN ENGLISH AND UZBEK (Journal of Universal Science Research, 2025)
This study investigates the lexicographic challenges involved in the bilingual treatment of specialized linguistic terms between English and Uzbek. Focusing on comparative analysis, the research examines structural and semantic differences in how linguistic terms are defined and presented in dictionaries and academic works.